2016
DOI: 10.3892/ol.2016.4220
|View full text |Cite
|
Sign up to set email alerts
|

Laccase purified from Cerrena unicolor exerts antitumor activity against leukemic cells

Abstract: Chronic lymphocytic leukemia (CLL) is the most commonly observed adult hematological malignancy in Western countries. Despite the fact that recent improvements in CLL treatment have led to an increased percentage of complete remissions, CLL remains an incurable disease. Cerrena unicolor is a novel fungal source of highly active extracellular laccase (ex-LAC) that is currently used in industry. However, to the best of our knowledge, no reports regarding its anti-leukemic activity have been published thus far. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…The supernatant was immediately subdivided into two fractions on the ultrafiltration system Pellicon 2 Mini holder (Millipore, Bedford, MA, USA) with an Ultracel mini cartridge (10 kD cut-off). The starting fraction containing compounds with a molecular weight below 10 kDa had already been used as a source of low molecular weight metabolites (extracellular low molecular weight subfraction, ex-LMS) and had been tested as described in our previous publication [ 32 ]. The antioxidant and pro-oxidative properties, the antibacterial, antiviral, immunomodulatory, and anticancer activities, and the toxicity of the ex-LMS fraction have also been presented in previously published reports [ 30 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was immediately subdivided into two fractions on the ultrafiltration system Pellicon 2 Mini holder (Millipore, Bedford, MA, USA) with an Ultracel mini cartridge (10 kD cut-off). The starting fraction containing compounds with a molecular weight below 10 kDa had already been used as a source of low molecular weight metabolites (extracellular low molecular weight subfraction, ex-LMS) and had been tested as described in our previous publication [ 32 ]. The antioxidant and pro-oxidative properties, the antibacterial, antiviral, immunomodulatory, and anticancer activities, and the toxicity of the ex-LMS fraction have also been presented in previously published reports [ 30 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…unicolor species possess cytotoxic and antiproliferative activity against cervical cancer cells (SiHa and CaSki) and melanomic cells [ 30 31 ]. The cytotoxic activity of laccase preparations towards several hematological malignancies has been described as well [ 32 ]. C .…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherent hematopoietic cells are frequently recognized as ex vivo sources of protein-based bioproducts applied in biotechnology, and biomedicine as well. Up to now, HL-60 cells as valuable human cells, have been applied as model in many studies on blood cells differentiation and physiology [14][15][16][17], or as a simple in vitro model in determination of cytotoxicity of anti-leukemic drugs [18,19]. But the efficiency of in vitro cultures of suspended biomass of HL-60 cells has not been extensively discussed so far, and the growth of HL-60 cells maintained in disposable bioreactor, as well as the influence of hydrodynamic conditions of the wave-type agitation on proliferation of HL-60 cells, has not been deeply studied or analysed up to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, hematopoietic cells are an acknowledged ex vivo source of bioproducts with many potential applications in bone marrow transplantation, immunotherapy, gene therapy, as well as the source of blood-derived products [13]. A HL-60 cell line, i.e., human acute promyelocytic leukemia cells, has been frequently applied as model of hematopoietic cells, and it was used in studies focused on in vitro blood cell formation [14], their physiology [15] and differentiation [16,17], as well as to studying the cytotoxicity effects of potential anti-leukemic drugs [18], or even in lab-on-a-chip applications [19]. Thus, an enhancement of HL-60 cells' propagation efficiency is a current research issue highly expected by representatives of a range of application niches, which experimentally involve such type of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies from our laboratory have shown that the ubiquitin-proteasome pathway is involved in the regulation of ligninolytic enzymes of white-rot fungi (such as laccase, benzenediol:oxygen oxidoreductase, EC 1.10.3.2) upon nutrient starvation [34][35][36] and in response to Cd 2+ exposure [33] and ER stress [37]. Lignin-degrading Basidiomycetes are increasingly being investigated due to their ecological significance and various potential applications of ligninolytic enzymes [38,39], especially laccase [40,41], in several industrial and biotechnological processes, including the application in the pulp and paper industry [42], enzymatic bioremediation [43], biosensor [44] and biofuel cell [45] construction, and medicine [46,47]. Numerous studies indicated that laccase production can be considerably stimulated by the presence of inducers, mainly aromatic or phenolic compounds related to lignin or lignin derivatives, such as ferulic acid, 2,5-xylidine, p-anisidine, or veratryl alcohol [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%